(3GdEOGQI GdPcjIs - (3YHO GdYRjR(B, (3GdfLGQs ((3YeGf(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2008)
(3jMJhj GdcJGH Ydi GdEOGQI GdPcjI hGdJNWjW , GdJfXje , EOGQI GdCaQGO , EJNGP GdbQGQGJ , jJMOK Yf GdeaGgje GdCSGSjI hGdeHGOF ddEOGQI hchfgG ef Cge CSHGH fLGM Ch aTd GdeTGQjY GdEbJUGOjI hGdJbOe Ch GdJNda GdEbJUGOj hGdMVGQj ddCee (B. (3hjVe agQS CHhGH GdcJGH (B: (3GdCYeGd hfXe GdCYeGd (B- (3GdbhGfjf GdCSGSjI aj GdEOGQI (B- (3EJNGP GdbQGQGJ (B- (3GdJNWjW (B- (3GdJfXje (B- (3GdJhLjg (B- (3GdQbGHI (B- (3EOGQI GdEfJGL (B- (3EOGQI GdJShb (B- (3GdEOGQI GdeGdjI (B- (3EOGQI GdCaQGO (B- (3EOGQI GdNOeGJ GdecJHjI (B- (3GdEOGQI GdYGeI (B- (3EOGQI GdTQcGJ GdYGeI (B- (3EOGQI GdeSJTajGJ (B- (3EOGQI GdTQWI (B- (3JWhQ GdacQ GdEOGQj (B- (3eQGLYI hJbjje GdEOGQI(B. s
Keywords: (3GJNGP GdbQGQGJs; (3GdEOGQIs; (3GdJNWjWs; (3fXe GdGYeGds